2023
DOI: 10.3389/fpls.2022.1105308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of planting and mowing cover crops as livestock feed on soil quality and pear production

Abstract: IntroductionThe increasing demand for animal-products has led to an increasing demand for livestock feed. Using cover crop as green manure in orchards is an effective measure to improve fruit yield and quality. However, the effect of mowing cover forage crops as livestock feed on soil quality and crop production is unclear.MethodTherefore, a 4-year field experiment, which included two treatments, was conducted in pear orchards in Luniao County, China: natural grass (NG) and planting and mowing forage crop ryeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The nexus between crop yield and SQI within the wheat‐maize planting system was strikingly apparent, underscoring the potent interplay between agricultural productivity and soil health. These findings resonated harmoniously with corroborative studies, such as those by Duddigan et al (2023), Fu et al (2022), and Zhang et al (2020), thus reinforcing the overarching impact of soil quality on crop yields. Furthermore, a coherent narrative emerges as the present research aligns seamlessly with antecedent investigations that denoted the region's soil quality as attaining a commendable moderate to upper echelon (Man et al, 2021; L. Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…The nexus between crop yield and SQI within the wheat‐maize planting system was strikingly apparent, underscoring the potent interplay between agricultural productivity and soil health. These findings resonated harmoniously with corroborative studies, such as those by Duddigan et al (2023), Fu et al (2022), and Zhang et al (2020), thus reinforcing the overarching impact of soil quality on crop yields. Furthermore, a coherent narrative emerges as the present research aligns seamlessly with antecedent investigations that denoted the region's soil quality as attaining a commendable moderate to upper echelon (Man et al, 2021; L. Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…Soil and plant enzymes, especially GS and nitrate reductase, play a vital role in improving crop nutrient transport, marking grain protein synthesis ( Li T. Y. et al., 2021 ). Green manure boosts soil enzyme activities related to nitrogen absorption and use, as well as these enzymes in leaves, aiding grain protein formation and nutrient content ( Fu et al., 2022 ). Nitrogen from decomposed green manures in soil forms a significant part of the nitrogen uptake in primary crops.…”
Section: The High-efficient Nitrogen Absorption and Utilization Mecha...mentioning
confidence: 99%
“…The fruit and soil samples were processed on the same day in July 2021. A soil sample at 0-40 cm soil depth was collected from each tree, which was a mix of the three soil replicates within the same plots, similar to Fu et al 20 The soil was air-dried to determine the soil properties according to the method used by Bao. 23 The soil pH was measured using a Delta 320 pH meter (Mettler-Toledo Instruments Co., Shanghai, China) with a soil:water ratio of 1:5.…”
Section: Description Of the Study Sitementioning
confidence: 99%
“…The Yangtze River Basin, one of the major pear districts, produces more than 80% of early ripening pears and 20% of the total pear yield in China. 20 Moreover, the climate in this area is warm and has a long frost-free period, making it suitable for grass growth. 21 Zhang et al 22 indicated that China's Yangtze River Basin region is rich in germplasm, with over 3000 natural herbage resources.…”
Section: Introductionmentioning
confidence: 99%